A Binary Access Control Scheme with Logical and Physical Keys - Islam, Md. Rafiqul; Selamat, Harihodin; Md. Sap, Mohd. Noor (Malaysian Journal of Computer Science, 2001)
An access control scheme for implementing the access control matrix is presented. The proposed scheme is based upon binary form of access rights and different from the schemes that are based on the concept of key-lock pairs. In this scheme, each user is assigned two keys. The first key is the logical key and is in binary form, and the second key is the physical key that holds access rights. The keys are possessed by the user, and can be used to derive the access rights to the files. The scheme has a special feature, such as a file or user can be added to or removed from the system without much effort. This scheme is more effective and efficient for systems where files are accessible to only a limited number of users.